2021
DOI: 10.1172/jci.insight.143007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a biological signature of prenatal maternal stress

Abstract: Psychological stress affects maternal gastrointestinal (GI) permeability, leading to low-grade inflammation, which can negatively affect fetal development. We investigated a panel of circulating markers as a biological signature of this stress exposure in pregnant women with and without the stress-related GI disorder irritable bowel syndrome (IBS). Markers of GI permeability and inflammation were measured in plasma from healthy and IBS cohorts of women at 15 and 20 weeks’ gestation. Biomarkers were evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Higher cerebrospinal fluid IL-1b, IL-23 and IL-33 concentrations at pre-cesarean time were significantly associated with increased odds of perinatal depression (37). Higher levels of TNF-α in depressed pregnant women were found when compared to controls in three studies (35, 38, 41). Nevertheless, these findings were not similar across all studies.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Higher cerebrospinal fluid IL-1b, IL-23 and IL-33 concentrations at pre-cesarean time were significantly associated with increased odds of perinatal depression (37). Higher levels of TNF-α in depressed pregnant women were found when compared to controls in three studies (35, 38, 41). Nevertheless, these findings were not similar across all studies.…”
Section: Resultsmentioning
confidence: 90%
“…In general, higher levels of mostly pro-inflammatory markers (namely, CRP, IFN-γ/IL-4 ratio, IL-1β, IL-1R, IL-5, IL-6, IL-8, IL-9, IL-12, IL-13, IL-23, IL-33 and TNF-α) were associated to higher depressive symptomatology or observed in depressed groups. For example, groups with higher depression symptoms demonstrated significantly higher circulating CRP levels (41) in comparison with those with lower depression symptom scores. Increased levels of CRP were also observed in a group with depression and trauma, in comparison to healthy pregnant volunteers (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,36 Three cohort studies investigated tryptophan and kynurenine in relation to levels of anxiety. 32,34,35 None of these studies found an association between tryptophan or kynurenine and anxiety symptoms during pregnancy. In all 3 studies the state of anxiety was measured using the State-Trait Anxiety Inventory (STAI).…”
Section: Maternal Pregnancy Outcomes Depression and Anxietymentioning
confidence: 99%
“…Tryptophan (Trp), as an essential amino acid, is mainly derived from the diet in the small intestine and, as the sole precursor of serotonin (5-HT), is directly and indirectly involved in modulating brain function [ 5 ], which plays a critical role in developing social-emotional behaviors in offspring [ 6 ]. The altered Trp metabolism is one of the core biological signatures of prenatal maternal stress [ 7 ] caused by intrauterine inflammation, increasing the potential risk of neurodevelopmental disorders (NDDs), such as autism spectrum disorders (ASD) [ 8 ], which is closely related to bullying in youth [ 9 , 10 , 11 ]. Urinary Trp and purine metabolites are consistently upregulated in the gestational diabetes mellitus patients [ 12 ], and excessive Trp compromises pregnancy, e.g., pre-eclampsia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%